Pengaruh Kualitas Informasi Media Sosial dan Kepercayaan terhadap Niat Berkunjung Wisatawan di Kota Makassar, Indonesia - Achmad Zulkarnain Zaenal; Zaenal Arifin Sahabuddin (Jurnal Simki Economic, 2023)
Social media information asymmetry has been viewed as an essential resource for travelers seeking out travel information. The purpose of this study is to determine how social media’s informational quality and trust affect travelers' intentions. Testing utilizing multiple regression analysis was conducted on 100 visitors to well-known tourist destinations in Makassar City, South Sulawesi, Indonesia. Using a questionnaire, data was gathered over the course of about two months. Empirical results show that social media information quality and trust positively influence tourist travel intentions in Makassar City. This study investigates the mechanisms by which the level of content that tourists create influences their trip intentions, which is advantageous for tourism management and marketing.